COVID-19 pandemic lessons for agri-food systems innovation - Barrett, Christopher B.; Fanzo, Jessica; Herrero, Mario; Mason-D'Croz, Daniel; Mathys, Alexander; Thornton, Philip K.; Wood, Stephen A.; Benton, Tim G.; Fan, Shenggen; Lawson-Lartego, Laté; Nelson, Rebecca; Shen, Jianbo; et al. (IOP Publishing, 2021)
The COVID-19 pandemic provides both a warning about agri-food systems' (AFS) functioning and an accelerator for AFS innovation. It revealed both the increasing frequency of extreme events and structural shortcomings with respect to access to healthy diets, equitable livelihoods, resilience, and climate and environmental sustainability challenges that pervade AFS worldwide (Barrett et al 2020). Return to prior state is both unlikely and undesirable. The central question is how will AFSs transform in response to the pandemic and the conditions it revealed? The pandemic has shifted awareness and incentives in ways that have the capacity—but are not guaranteed—to prompt necessary, transformational AFS adaptation (Kates et al 2012, Bassett and Fogelman 2013). Will AFS transformation occur and, if so, who will benefit and who will bear the costs and risks? Drawing on a year-long global expert panel review (Barrett et al 2020) we summarize the evidence on AFS impacts of the pandemic and offer seven key lessons to guide adjustments to policies and practices.